Obstetric admission and maternal mortality in the intensive care unit in Africa: A systematic review and meta-analysis - Alemwork Abie; Molla Getie Mehari; Tenagnework Eseyneh Dagnew; Amare Mebrat Delie; Mihret Melese; Liknaw Workie Limenh; Nigus Kassie Worku; Eneyew Talie Fenta; Dereje Esubalew; Mickiale Hailu (PLoS ONE, 2025)
Background Obstetric complications are a major contributor to maternal morbidity and mortality worldwide, especially in low-resource settings such as many countries in Africa. Intensive care units offer specialized care for women with severe obstetric complications, which require advanced monitoring and therapeutic interventions. Despite the critical importance of ICU care, there is a paucity of comprehensive data on obstetric ICU admissions and outcomes in Africa. Therefore, this study aimed to assess the proportion of obstetric admissions and maternal mortality in the intensive care unit in Africa. Objective To assess the proportion of obstetric admissions and maternal mortality in the intensive care unit in Africa. Methodology The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA 2020) guidelines were followed in reporting the study’s findings. Articles searched; from PubMed, HINARI, Web of Science, Google Scholar, Repository, and African Journals Online were systematically searched for reports of obstetric admission in the intensive care unit, either pregnant or up to 6 weeks postpartum. The Joanna Briggs Institute (JBI) Critical Appraisal tool was used to evaluate each article’s quality. The Stata 17 software was used to compute the analysis. The heterogeneity of the studies was detected using the Cochran Q test and I2 test statistics, which were considered significant at p < 0.05. The random effect model of analysis was used with evidence of heterogeneity. Egger’s test at p < 0.05 was used to check the evidence of publication bias within the studies. Subgroup analysis and sensitivity analysis were done. Result Eleven studies were included in this study with a total of 10,190 mothers admitted to the intensive care unit. The overall pooled proportion of obstetric intensive care unit admissions in Africa was 17.22% (95% CI; 12.97–21.47; I2 = 97.63%). This translates to roughly 17 out of every 100 ICU admissions being for obstetric complications. Hypertensive disorders of pregnancy 42.96% (95% CI: 27.3, 58.56) and obstetric hemorrhage 24.15% (95% CI: 18.12, 30.18) were the common indications for obstetric admission in the intensive care unit.. Maternal mortality among ICU-admitted patients reached a concerning 30.69% (95% CI: 23.16, 38.22; I2= 93.34%). This means that, nearly one in three women admitted to the ICU for obstetric complications died. Conclusion In Africa, the proportion of obstetric admissions and maternal mortality in the intensive care unit is significant. This high percentage of obstetric admissions and maternal mortality in the ICU highlights the necessity to enhance emergency obstetric care services and invest in the development of well-equipped obstetric ICUs to reduce maternal mortality. Registration CRD42024516612.